What are the factors associated with human immunodeficiency virus/sexually transmitted infection screening behaviour among heterosexual men patronising entertainment establishments who engaged in casual or paid sex? – Results from a cross-sectional survey in an Asian urban setting. Issue 1 (December 2016) - Lim, Raymond; Tham, Dede; Cheung, Olive; Tai, Bee; Chan, Roy; Wong, Mee
Abstract Background Late presentation of human immunodeficiency virus (HIV) is associated with heterosexual transmission, particularly among heterosexual men in Asia. Although data on HIV/sexually transmitted infection (STI) testing behaviour is increasing, information is still lacking among heterosexual men who receive far lesser attention and are generally invisible in HIV/ STI prevention, particularly in the Asian urban setting. The aim of this study was to assess the prevalence of HIV/STI testing among heterosexual men patronising entertainment establishments (EEs) who engaged in casual or paid sex in Singapore, and the factors associated with this behaviour. Methods This was a cross-sectional survey involving 604 participants using time location sampling between March and May 2015. For multivariable analysis, we used a mixed effects Poisson regression model with backward stepwise approach to account for clustering by venue and to obtain the adjusted prevalence ratio (aPR) for the association of various factors with HIV/STI testing. Results Among 604 at-risk participants, only 163 (27.0%) had gone for HIV or STI testing in the past 6 months. Of this, 83.4% of them specifically underwent HIV testing. In multivariable analysis, HIV/STI testing increased with being non-Chinese (aPR 1.50; 95% CI: 1.08–2.06), having engaged in anal sex with casual or paid partner in the past 6 months (aPR 1.80; 95% CI: 1.27–2.57), number of partners in the past 6 months (aPR 1.03; 95% CI: 1.01–1.05) and HIV knowledge score (aPR 1.11; 95% CI: 1.05–1.16). Among those who reported non-consistent condom use with casual or paid partner, almost half of them (47.9%) perceived that they were at low risk for HIV/STI. Sigmatisation and discrimination was another common barrier for non-testing. Conclusions Despite being at risk of HIV/STI, the low prevalence of testing coupled with a high prevalence of risky sexual behaviour among this group of heterosexual men in Singapore calls for a need for HIV/STI prevention interventions in the EE setting. Other than promoting testing and safer sex, the interventions should address the discordance between perceived risk and actual sexual behaviour, in addition to the stigma and discrimination associated with testing for this group.